Effect of changing suction on shear strength of unsaturated soil - Syaiful Marzuki Roslan, 1981-; Nurly Gofar, supervisor; Fakulti Kejuruteraan Awam (2012)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2012